THE IDEA OF CONTINUITY IN THE NOVELS OF I.S. TURGENEV (Proceedings of Southern Federal University. Philology, 2022)
DOI 10.18522/1995-0640-2022-4-102-118The article poses the problem of comprehending the epic nature of the novels by I.S. Turgenev, which in literary criticism are considered the most capacious, concise, and also saturated with lyricism. It is noted that Turgenev, who turned to the model of the Russian world in “Notes of a Hunter”, found the idea of epic synthesis with great difficulty, could not easily abandon it. It is proved that the novel “Two Generations” destroyed by the writer was a “grain” from which many plot lines and motifs of the subsequent novels of the writer grew, a kind of afterword to which “The Story of Father Alexei” can be considered. The author of the article analyzes the actions, behavioral characteristics of the characters and events that contribute to understanding the scale of the writer's novels, which are not limited to socio-political issues. Turgenev's idea of ​​continuity, the idea of the cyclical nature of life, the rhythm of the work, a well-thought-out system of characters, and an increased citation of the finals of novels play a paramount role in organizing the epic dominant of the genre in Turgenev.Keywords: Turgenev, novel, epic dominant, continuity, national identity, traditions, hero system, cyclicity, religious consciousness, artistic evolutionAcknowledgments: The reported study was funded by RFBR, project number 20-012-00102